2020
DOI: 10.3390/joitmc6030084
|View full text |Cite
|
Sign up to set email alerts
|

Trouble in Paradise? Barriers to Open Innovation in Regional Clusters in the Era of the 4th Industrial Revolution

Abstract: The purpose of this paper is to provide an insight into the barriers faced by clusters as open innovation intermediaries. Literature review and an empirical study were performed, involving a nation-wide survey, case studies, and in-depth interviews with cluster actors involved in open innovation activities. This article conceptually links open innovation and clusters in the context of the fourth industrial revolution, empirically identifies barriers hindering open innovation in clusters, and indicates factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
(80 reference statements)
2
10
0
Order By: Relevance
“…Regarding environmental factors, external support has a significant effect on BDA adoption, which was concluded in previous investigations [129] and is consistent with studies that indicate that open innovation requires external collaboration [87,[130][131][132], while competitive pressure has a negligible effect on BDA adoption, consistent with the…”
Section: Discussion: Big Data and Open Innovationsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding environmental factors, external support has a significant effect on BDA adoption, which was concluded in previous investigations [129] and is consistent with studies that indicate that open innovation requires external collaboration [87,[130][131][132], while competitive pressure has a negligible effect on BDA adoption, consistent with the…”
Section: Discussion: Big Data and Open Innovationsupporting
confidence: 91%
“…Regarding environmental factors, external support has a significant effect on BDA adoption, which was concluded in previous investigations [129] and is consistent with studies that indicate that open innovation requires external collaboration [87,[130][131][132], while competitive pressure has a negligible effect on BDA adoption, consistent with the results of other studies [33] but inconsistent with other results [31,133]. This may be due to the early stage of adoption in HEIs, which are using BDA as a process of learning and verifying its potential and not as a necessity triggered by competitive pressure.…”
Section: Discussion: Big Data and Open Innovationsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the unequivocal benefits associated with the practices of innovation in SMEs, studies have also shown that these types of companies have greater difficulty in developing mechanisms capable of effectively implementing open innovation due to their size [75,76]. In these studies, it was emphasized that the greater flexibility and adaptability of these organizations did not compensate for the lack of resources and skills to develop a culture of permanent innovation.…”
Section: The Relevance Of Open Innovation In Smesmentioning
confidence: 99%
“…High-tech industrial development zones (hereinafter referred to as "high-tech zones") are special areas that rely on policies and environmental advantages to aggregate innovative resources to promote the development of high-tech industries. From a global perspective, the high-tech zone has become the preferred development mode for various countries and regions to create innovation highlands, cultivate innovative enterprises, build innovation ecology, improve innovation performance, and lead economic innovation driven development [1,2].…”
Section: The Introductionmentioning
confidence: 99%